Hubungan Kualitas Tidur Dan Stres Dengan Tekanan Darah Lansia Di Desa Puton Kecamatan Diwek Kabupaten Jombang - Praningsih, Supriliyah; Siswati; Maryati, Heni; Priyanti, Ratna Puji (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Hypertension is a disease that causes death silently or is called a silent killer. Many people with hypertension are not aware of the symptoms and problems that occur because there are no warning signs or symptoms (WHO, 2021). Risk factors that can affect the incidence of hypertension include sleep quality and stress. The purpose of this study was to determine the relationship between sleep quality and stress with blood pressure. Methods: This article design used correlational research with a "Cross Sectional" approach. The population of this study was the elderly in Puton Village, Diwek District, Jombang Regency, totaling 35 people. Sleep quality and stress were measured using a questionnaire. Blood pressure was measured using a sphygmomanometer according to standard guidelines. Data analysis by editing, coding, scoring, tabulation and statistical tests were carried out using the Spearman Rank test. Results: Most respondents have poor sleep quality. Most respondents are normal, not experiencing stress. Most respondents have systolic blood pressure with grade 1 hypertension. almost half of respondents have diastolic blood pressure with grade 1 hypertension and grade 2 hypertension. The results of the analysis between sleep quality and systolic and diastolic blood pressure obtained a p value> 0.05 which indicated that there was no relationship between sleep quality and blood pressure, both systolic and diastolic. This is the same as the relationship between stress with systolic and diastolic blood pressure, where the test results obtained a p value> 0.05 which indicates that there was no relationship between stress and blood pressure, either systolic or diastolic Conclusion: In addition to sleep quality and stress, there are other factors that affect blood pressure that cannot be controlled by researchers that have an impact on changes in blood pressure. Controlling the role factors is very necessary to obtain significant results.